건물 외피의 진공단열패널 시공방식에 따른 단열성능 분석 - 김상명(Sang Myung Kim); 김진희(Jin Hee Kim); 김준태(Jun Tae Kim) (KIEAE Journal, 2024)
Purpose: Vacuum insulation panels (VIPs) are among the high-efficiency insulation materials with a thermal conductivity of approximately 0.002W/mK. VIPs have an insulation performance approximately eight times higher than that of conventional building insulation materials, allowing buildings to meet insulation standards with only a thin layer when applied to building envelopes. However, VIPs can cause thermal bridging in various aspects when applied to buildings, which can reduce the insulation performance of building envelopes. For this reason, this paper investigates the types of thermal bridges associated with VIPs and analyzes the thermal bridging and insulation performance based on different installation methods of VIPs. Method: For this study, building envelopes were designed and constructed using two different VIP installation methods. The insulation performance of building envelopes with VIPs was compared and analyzed through thermal transmittance experiments and thermal analysis simulations. Result: This paper confirms that the construction method of vacuum insulation panels is important for reducing thermal bridges and maintaining high insulation performance. KCI Citation Count: 0